The impact of online marketing on tourists' visit intention: Mediating roles of trust - Anfitri Sihombing; Li-Wei Liu; Pahrudin Pahrudin (Journal of Tourism, Heritage & Services Marketing)
Purpose: Making social media the landscape of travel decision-making has a significant transformation, and become adept at catering to the specific needs and preferences of travelers. This study examined the impact of online marketing on tourists’ visit intention: mediating roles of trust. The study investigated the relationship among electronic word of mouth (eWoM), customer online reviews, official website reviews, and travel intention.